2004
DOI: 10.1074/jbc.m310859200
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Fragments Stimulate Endothelial Recognition of Injury through TLR4

Abstract: Tissues must quickly recognize injury to respond to the rapid pace of microbial growth. In skin, dermal microvascular endothelial cells must also react to danger signals from the surrounding tissue and immediately participate by initiating the wound repair process. Components of the extracellular matrix such as hyaluronan are rapidly broken down into smaller molecular weight oligosaccharides in a wound, and these can activate a variety of biological processes. This study set out to determine if hyaluronan frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
392
3
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(421 citation statements)
references
References 38 publications
16
392
3
10
Order By: Relevance
“…However, in normal chondrocytes the effect exerted by low molecular HA was not found to be so high, although significant [15][16], compared with the effect obtained by other Authors in different cell types [2,17,[32][33][34], and this was probably due to the different size of the HA fragment used. In addition, the studies using chondrocytes separately evaluated TLR-4 or CD44 receptor involvement [15][16] and there was no information available on the evaluation of both these receptors by HA fragment stimulation in chondrocytes.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…However, in normal chondrocytes the effect exerted by low molecular HA was not found to be so high, although significant [15][16], compared with the effect obtained by other Authors in different cell types [2,17,[32][33][34], and this was probably due to the different size of the HA fragment used. In addition, the studies using chondrocytes separately evaluated TLR-4 or CD44 receptor involvement [15][16] and there was no information available on the evaluation of both these receptors by HA fragment stimulation in chondrocytes.…”
Section: Discussioncontrasting
confidence: 55%
“…The identification of the TLR-4 and CD44 receptors as the target for 6-mer HA had previously been demonstrated by several studies [2,[17][18][30][31][32][33]. We recently reported that low molecular weight HA was able to stimulate inflammation in normal articular mouse chondrocytes [15][16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These include cellular molecules that directly activate the complement cascade 66,67 or cleave extracellular matrix molecules such as collagen 68 69, fibrillar protein 70 , hyaluronic acid 71 and heparan sulfate 72 into proinflammatory fragments. Cellular molecules may also trigger the clotting, fibrinolytic and kinin cascades which generate other proinflammatory mediators 73 .…”
Section: Extracellular Damps and Other Mediatorsmentioning
confidence: 99%
“…Hyaluronan, a ubiquitously present constituent of the extracellular matrix [281], exists as a high molecular weight polymer under physiologic conditions, but undergoes degradation resulting in accumulation of lower molecular weight species after tissue injury. Hyaluronan fragments induce the expression of a variety of inflammatory genes by endothelial cells and macrophages [282], including chemokines and cytokines, and may play an important role in regulating inflammatory processes. Furthermore, clearance of hyaluronan fragments from the injured tissue is crucial for resolution of chronic inflammation [283].…”
Section: Clearance Of Apoptotic Neutrophils and Removal Of Matrix Debrismentioning
confidence: 99%